Upsilon suppression in the QGP at the LHC - Wolschin, Georg (Nuclear physics. A, Nuclear and hadronic physics, 2016)
The suppression of ϒ-mesons in the hot quark-gluon medium in PbPb collisions is accounted for in a model that encompasses gluodissociation, collisional damping, screening, and reduced feed-down. Theoretical results for centrality-dependent suppression factors of the ϒ(1S) and ϒ(2S) states are compared with CMS data. The measured ground state suppression is well represented, but discrepancies between data and model persist for peripheral ϒ(2S)-events that require additional suppression mechanisms. The pT-dependence of the suppression is discussed and a prediction for the centrality-dependent ϒ(1S) suppression in 5.02 TeV PbPb is made.
Gesehen am 29.11.2017